Предмет: Алгебра,
автор: pekarevhrom
1)Решите уравнение х-х^=0
2)Известно, что 2(3х+а)^=18x^+60x+2a^ Найдите а
Ответы
Автор ответа:
0
х-х^=0 х(1-х)=0 х=0 1-х=0,то х=1
2(3х+а)^=18х^+60 х+2а^
2(9х^+6aх+а^)=18х^+60х+2а^
18х^+12ах+2а^=18х^+60х+2а^
18х^ +12ах +2а^-18х^-60х-2а^=0
12ах-60х=0
12х(а-60)=0 12х=0
а-60=0 а=60
2(3х+а)^=18х^+60 х+2а^
2(9х^+6aх+а^)=18х^+60х+2а^
18х^+12ах+2а^=18х^+60х+2а^
18х^ +12ах +2а^-18х^-60х-2а^=0
12ах-60х=0
12х(а-60)=0 12х=0
а-60=0 а=60
Похожие вопросы
Предмет: Алгебра,
автор: agyha2455
Предмет: Русский язык,
автор: dlfnuvj
Предмет: Алгебра,
автор: heavenlyswan
Предмет: Алгебра,
автор: Аноним
Предмет: Геометрия,
автор: Yanojka